Legal Consequences of a House Sale and Purchase Agreement Through a Home Ownership Credit by Over Credit Underhand - Purwandini, Dewi Fitriasih; Sri Darmadi, Nanang (Sultan Agung Notary Law Review, 2024)
This study aims to analyze: 1) The legal consequences of a house sale and purchase agreement through a mortgage underhand over credit for the parties. 2) Legal protection for the parties due to an over credit sale and purchase agreement. The approach methods used in this study are the case study approach and the statute approach. This type of research is a normative legal research. The types and sources of data in this study are secondary data obtained through literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) The legal consequences of a house sale and purchase agreement through a mortgage underhand over credit for the parties carried out with trust in each other, because this trust is not based on applicable law will harm the party who receives the debtor. The loss can be in the form of default. The legal consequence of the default is that the replacement debtor cannot take the certificate that is still in the bank's possession. The replacement debtor cannot change the name, because the certificate is still registered in the name of the first debtor. 2) Legal protection for the parties due to the over credit sale and purchase agreement, namely preventive protection for the buyer can be carried out in the implementation of the sale and purchase agreement by checking the existence of evidence of ownership of land rights that are the object of the agreement. Repressive protection in decision Number 30 / Pdt.G / 2016 / PN.Cbn is by filing a lawsuit with the Court. In this decision, the Plaintiff or buyer asked the Cirebon District Court so that the decision can be used to take the KPR house certificate that is still under the control of the Bank and carry out the name change process. In his decision, the judge stated that the KPR house purchased by the plaintiff was valid and had permanent legal force. The judge also stated that the buyer was a buyer in good faith for the object of the dispute. One of the principles in a sale and purchase agreement is that buyers in good faith must always be protected.